2011
DOI: 10.1177/1545109711422124
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Preexisting Major Protease Inhibitor Resistance Mutations are Associated with Virologic Failure of a Dual-Class Antiretroviral Regimen with Inhibitors of HIV-1 Viral Protease and Integrase

Abstract: Most treatment-experienced individuals achieved virologic suppression on a dual-class regimen of a PI plus raltegravir. Success was limited by poor medication adherence and preexisting major PI resistance mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Five other uncontrolled studies describing a switch to raltegravir and boosted or unboosted PI reported good results but the evidence graded as insufficient [67]–[71]. A varying percentage of participants with an undetectable viral load at start of those studies (63% to 100%), different outcome measures and study duration, all hampered uniform conclusions.…”
Section: Resultsmentioning
confidence: 99%
“…Five other uncontrolled studies describing a switch to raltegravir and boosted or unboosted PI reported good results but the evidence graded as insufficient [67]–[71]. A varying percentage of participants with an undetectable viral load at start of those studies (63% to 100%), different outcome measures and study duration, all hampered uniform conclusions.…”
Section: Resultsmentioning
confidence: 99%
“…[27][28][29] In those studies, patients who refilled ARVs at a rate higher than 85% of the times were more likely to experience viral suppression than those who reported lower refill rates. 10,25 All used strategies that need longer periods of observation to detect failures in adherence. However, the delay to pick up ARVs can be detected month by month during the pharmacists' attendance, since dispensing of ARV drugs in the Brazilian public health system is most often conducted on a monthly basis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, looking at pharmacy records and its correlation with HIV viral load (VL) and CD4 þ cell count could be a feasible strategy for the assessment of adherence in these settings. 10,11 A consistent pharmacy dispense report for ARV drugs with regular monitoring of an undetectable VL and a preserved CD4 þ cell count would provide a useful strategy to monitor for adherence to ARV therapy. Monitoring pharmacy records is an indirect method to assess adherence and thus can be more exposed to biases since a patient can accurately refill his/her medications every month but not necessarily be taking them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation